Preparation and characterization of a sulfonated carbon-based solid acid microspheric material (SCSAM) and its use for the esterification of oleic acid with methanol - Zhang, Honglei; Luo, Xiang; Chen, George Z.; He, Feng; Wu, Tao (Austin Publishing Group, 2016)
In this study, a sulfonated group (-SO3H) rich carbon-based solid acid microspheric material was prepared by hydrothermal method followed by sulfonation using glucose as the raw material. Such a green, non-corrosive, and renewable carbon material was used as a heterogeneous catalyst for the esterification of oleic acid with methanol for the production of biodiesel. The carbon microspheres were characterized systematically. It was found that the carbon microspheres prepared under the optimal reaction conditions exhibited smooth surfaces, uniform particle sizes and good dispersion. The sulfonated carbon-based solid acid microspheric materials showed high acidity and good catalytic activities for the esterification of oleic acid with methanol. The influence of reaction operating conditions on the performance of esterification was studied. The optimal esterification reaction conditions were found to be: methanol/oleic acid molar ratio 12:1, catalyst loading 0.25 g (0.05 mmol H+), reaction temperature 65 °C, reaction time 8 h and mechanical stirring rate 360 rpm. It was found that the catalyst demonstrated very good reusability although there was noticeable loss in acidity due to the leaching of active sites.